Developing a GIS based method for school site identification in the rural Eastern Cape - Swart, Conrad Dirk (Rhodes University, Faculty of Science, Department of Geography, 2015)
Historically, South Africa has not had equal education in terms of funding, curriculum or physical resources and structures. These issues are still present in contemporary South Africa and none more so than the issues surrounding "mud schools" . Recently the Department of Basic Education (DBE) implemented a plan to eradicate inappropriate school structures using the Accelerated Schools Infrastructure Delivery Initiative program (ASIDI). Questions around effective placement of schools are now being asked. Using interviews and analysis of literature, this research developed criteria needed to determine how rural school sites are selected. Geographical Information Systems (GIS) was used to determine if current sites are in the most appropriate areas. The results of the research included a unique set of Eastern Cape criteria as well as an analysis of the current site selection methods used by the DBE. It also revealed that most of the schools are being constructed in acceptable areas. The main result that emerged from the research was that schools will be placed in areas where they are needed. Developing site selection criteria is still needed as South Africa seeks to reduce the education gap between rich and poor schools.
Keywords: Geographic information systems -- South Africa -- Eastern Cape; School sites -- South Africa -- Eastern Cape; School sites -- South Africa -- Eastern Cape -- Planning; Rural schools -- South Africa -- Eastern Cape